Political communication in post-truth society - Gorenc, Nina (Ars et humanitas, 2020)
The research behind this paper is set in the context of the 2016 US presidential election that has come to symbolize the post-truth era. We conducted a literature review on the 2016 election, with the aim to better understand the impact of computational propaganda on the election outcome and on the behaviour of voters. The paper opens with a definition of post-truth society and related concepts such as fake news and computational propaganda. It explores the changes of political communication in a digital environment and analyses the role of social media in the 2016 election. It probes into phenomena such as the trivialization of politics and the loss of credibility of political actors, which are both common in post-truth societies. The reviewed literature seems to indicate that social media have become strong actors on the political stage, but so far not the predominant source of political information and influence on the behaviour of voters. The paper makes two important contributions. Firstly, drawing on the concept of post-truth society, it analyses the role of computational propaganda in the 2016 presidential election, and secondly, it attempts to explain the paradox of general political apathy on one hand, and increased political activism on the other. These are some of the challenges we are now facing, and in order to be able to cope with them it is important to acknowledge and understand them
Keywords: boti; lažne novice; Political communication; politična propaganda; Politično komuniciranje; postresničnost; računalniška propaganda